Why we die - Herron, Mick (Carroll & Graf Publishers, 2006)
When Tim Whitby checks into a hotel, he's not intending to check out again <U+2014> but then he meets Katrina Blake, a woman in need of rescue. When Arkle, Baxter and Trent inherit the family business, they're not planning on making a go of it <U+2014> there are quicker ways of getting rich, if you're not squeamish about the violence involved. And when Zoë Boehm agrees to track down the the masked men who robbed Harold Sweeney's jewellery shop, she's hoping to pay off the taxes she's avoided. She's not expecting to wind up in a coffin. But Arkle has a crossbow; Tim has a life that's run out of purpose, and even battered Katrina has her secrets. And death, like taxes, can't be avoided forever.